About Phaedra: nowadays theatrical productions on a classical myth (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
Just like several mythical characters from antiquity, Phaedra is linked to a common idea of a cursed woman, devastated by a incestuous erotic passion. This paper would discuss the holding of such preconception in Italian theatrical productions from the Eighties to nowadays, beginning from Luca Ronconi’s direction, who reintroduces the theme in contemporary Italian theatre. Henceforth, a sequence of productions based on the main rewritings of the myth (Racine, D’Annunzio, Kane, but also Seneca and Euripide) brings to light unreleased features and current implications.
Keywords: Phaedra; Ronconi; Castri; Sciaccaluga; De Rosa